The GFDL Earth System Model Version 4.1 (GFDL‐ESM 4.1): Overall Coupled Model Description and Simulation Characteristics. (19th November 2020) - Dunne, J. P.; Horowitz, L. W.; Adcroft, A. J.; Ginoux, P.; Held, I. M.; John, J. G.; Krasting, J. P.; Malyshev, S.; Naik, V.; Paulot, F.; Shevliakova, E.; Stock, C. A.; et al.
Abstract: We describe the baseline coupled model configuration and simulation characteristics of GFDL's Earth System Model Version 4.1 (ESM4.1), which builds on component and coupled model developments at GFDL over 2013–2018 for coupled carbon‐chemistry‐climate simulation contributing to the sixth phase of the Coupled Model Intercomparison Project. In contrast with GFDL's CM4.0 development effort that focuses on ocean resolution for physical climate, ESM4.1 focuses on comprehensiveness of Earth system interactions. ESM4.1 features doubled horizontal resolution of both atmosphere (2° to 1°) and ocean (1° to 0.5°) relative to GFDL's previous‐generation coupled ESM2‐carbon and CM3‐chemistry models. ESM4.1 brings together key representational advances in CM4.0 dynamics and physics along with those in aerosols and their precursor emissions, land ecosystem vegetation and canopy competition, and multiday fire; ocean ecological and biogeochemical interactions, comprehensive land‐atmosphere‐ocean cycling of CO2, dust and iron, and interactive ocean‐atmosphere nitrogen cycling are described in detail across this volume of JAMES and presented here in terms of the overall coupling and resulting fidelity. ESM4.1 provides much improved fidelity in CO2 and chemistry over ESM2 and CM3, captures most of CM4.0's baseline simulations characteristics, and notably improves on CM4.0 in (1) Southern Ocean mode and intermediate water ventilation, (2) Southern Ocean aerosols, and (3) reduced spurious ocean heat uptake. ESM4.1 has reduced transient and equilibrium climate sensitivity compared to CM4.0. Fidelity concerns include (1) moderate degradation in sea surface temperature biases, (2) degradation in aerosols in some regions, and (3) strong centennial scale climate modulation by Southern Ocean convection. Plain Language Summary: GFDL has developed a coupled chemistry‐carbon‐climate Earth System Model (ESM4.1) as part of its fourth‐generation coupled model development activities with model results contributed publicly to the sixth phase of the Coupled Model Intercomparison Project. With similar computational expense as GFDL's first coupled model CM4.0, ESM4.1 focuses on chemistry and ecosystem comprehensiveness rather than the ocean resolution‐focus of CM4.0. With fidelity near to that of CM4.0, ESM4.1 features much improved representation of climate mean patterns and variability from previous GFDL ESMs as well as comprehensive couplings for chemistry, carbon, and dust. Key Points: A new coupled chemistry‐carbon‐climate Earth system model has been developed at the Geophysical Fluid Dynamics Laboratory This model unifies component advances in chemistry, carbon, and ecosystem comprehensiveness within a single coupled climate framework This model features much improved climate mean patterns and variability from previous chemistry and carbon coupled models